2021
DOI: 10.3897/neobiota.67.59134
|View full text |Cite
|
Sign up to set email alerts
|

Biological invasions in France: Alarming costs and even more alarming knowledge gaps

Abstract: The ever-increasing number of introduced species profoundly threatens global biodiversity. While the ecological and evolutionary consequences of invasive alien species are receiving increasing attention, their economic impacts have largely remained understudied, especially in France. Here, we aimed at providing a general overview of the monetary losses (damages caused by) and expenditures (management of) associated with invasive alien species in France. This country has a long history of alien species presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 82 publications
(103 reference statements)
4
35
0
Order By: Relevance
“…resulted in a high percentage of cost entries reported in Spanish (98%), consistent with findings in some other European countries that reported costs in their native language (e.g. 97% for France, Renault et al 2021; 69% for Germany, Haubrock et al 2021b). For instance, in Central and South America over 40% of cost estimates came from Spanish and Portuguese sources (Heringer et al 2021); and in Ecuador 51.8% of the costs were reported in Spanish (Ballesteros-Mejia et al 2021).…”
Section: General Costs Of Ias In Spainsupporting
confidence: 86%
“…resulted in a high percentage of cost entries reported in Spanish (98%), consistent with findings in some other European countries that reported costs in their native language (e.g. 97% for France, Renault et al 2021; 69% for Germany, Haubrock et al 2021b). For instance, in Central and South America over 40% of cost estimates came from Spanish and Portuguese sources (Heringer et al 2021); and in Ecuador 51.8% of the costs were reported in Spanish (Ballesteros-Mejia et al 2021).…”
Section: General Costs Of Ias In Spainsupporting
confidence: 86%
“…However, InvaCost only reported cost data for 35 species, suggesting a huge underestimation of invasion costs in Mexico -since costs are available for only 10% of known IAS. This proportion is similar to that reported in other studies, which have found that less than 10% of invaders have reported costs: Germany , France (Renault et al 2021), the United Kingdom, (Cuthbert et al 2021b), Asia (Liu et al 2021), Argentina (Duboscq-Carra et al 2021 or Australia (Bradshaw et al 2021). Even if one cannot conclude that actual costs should be ten times higher, the very high overall economic costs we found for only 10% of IAS in Mexico hints at a real, total cost that is staggering.…”
Section: Discussionsupporting
confidence: 89%
“…According to Contreras-Balderas and Gutiérrez (2009), at least 36 of the IUCN 100 of the world's worst IAS (van der Weijden et al 2007) are established in Mexico, and many of them were included in the present study, such as Eichhornia crassipes, Arundo donax, L. catesbeianus, Felis catus, Capra hircus, Mus musculus, Rattus rattus, among others, and are particularly economically costly (Cuthbert et al 2021a). E. crassipes and A. donax were also among the costliest species in Spain (Angulo et al 2021b), while mammals appear to be also very costly in other countries such as France (Rattus and Felis, (Renault et al 2021)), Japan (Rattus, (Watari et al 2021)) or Ecuador (Capra and Rattus, (Ballesteros-Mejia et al 2021)), mainly due to the management of these species in islands (e.g. invasive rodents, (Diagne et al 2021a)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we showed that this is a general pattern in the region, with Singapore amongst the countries with most cost entries in Southeast Asia. Second, national or regional studies on the economic costs of biological invasions outside this region also consistently reported only between 2% and 10% of invasive alien species having recorded costs, for example, Argentina (Duboscq-Carra et al 20201), Asia (Liu et al 2021), Australia (Bradshaw et al 2021), France (Renault et al 2021), Germany (Haubrock et al 2021c), Mexico (Rico-Sánchez et al 2021 and United Kingdom (Cuthbert et al 2021a).…”
Section: Discussionmentioning
confidence: 99%